FACTORS INFLUENCING UNDERGRADUATE STUDENTSâ INTENTION TO USE CHAT GPT PLUS - Mahasti Kayla, Selvarani
Chat GPT and Chat GPT Plus have gained attention as chatbot services in educational contexts. This study aims to identify the factors influencing undergraduate students' intention to use Chat GPT Plus using a comprehensive approach that combines qualitative and quantitative analyses. The qualitative phase utilizes automated coding with NVivo software, while the quantitative phase employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research focuses on undergraduate students residing in Bandung and Jakarta who have experience using Chat GPT or Chat GPT Plus, with 10 respondents for qualitative analysis and 243 respondents for quantitative analysis. The qualitative phase explores additional variables, such as social influences for Chat GPT, and habit, priority access, and cost-efficient value for Chat GPT Plus. The findings indicate that relative advantages, compatibility, complexity, and social influences significantly influence undergraduate students' intention to use Chat GPT, while habit, priority access, and cost-effectiveness and value significantly influence their intention to use Chat GPT Plus. The results of this research are expected to provide insights for further understanding and inform decision-making in the implementation of these chatbot services in educational settings.